Technology-Mediated Task-Based Language Teaching at Private Universities in Bangladesh: Students' and Teachers' Perceptions (Pascasarjana Universitas Negeri Makassar, 2022)
Task-based language teaching (TBLT) facilitates the process of language learning by focusing on communicative skills in real life. The English language teaching (ELT) system at the private universities of Bangladesh is trying to integrate TBLT with technology nowadays. This study aims to explore the proportion of successful implications of technology and tasks, the perceptions of teachers and learners regarding technology-mediated tasks, the challenges faced by both sides and recommendations to overcome limitations at three private universities in Bangladesh. Besides, this study identifies the task patterns used by teachers as well as the types of tasks preferred by students. Both qualitative and quantitative methods were applied to conduct this study. Data were collected from the teachers and learners of Pundra University of Science & Technology, Bogura; Varendra University, Rajshahi; and Rabindra Maitree University, Kushtia by providing them with Google Docs semi-structured questionnaires. The teachers of the department of English, and the students of the department of English, Computer Science Engineering (CSE) and Business Administration participated in the data collection procedure. The study found that technology-mediated TBLT is implemented alongside traditional teaching methods in language teaching. Students appreciate technology-based tasks in learning a target language. They recommend more skilled and experienced teachers. Teachers suggest that financial funding and skilled IT officers are needed to implement TBLT. Poor internet connection, inadequate technological support, faulty projectors and sound systems are the difficulties faced by teachers and students.